EVALUATION OF THE IMPLEMENTATION OF PERMENDAGRI NO. 20 OF 2018 IN VILLAGE FINANCIAL MANAGEMENT: A CASE STUDY OF PEMUDA VILLAGE - Astia Putriana; Yasir Hadiani; Mellisa Anggraini (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
This study aims to evaluate the financial management of Desa Pemuda based on Permendagri No. 20 of 2018 concerning village financial management. The regulation outlines five key stages: planning, implementation, administration, reporting, and accountability. Financial management in villages must be carried out in a transparent, accountable, participatory manner, and in accordance with budget discipline. This study was conducted to determine whether the financial management practices in Desa Pemuda align with the provisions of the regulation. This research uses a qualitative descriptive method. Data were collected through interviews with village officials, analysis of supporting documents, and field observations. The evaluation indicators were developed based on the regulatory framework and were used to assess compliance at each stage. The results show that the financial management of Desa Pemuda has generally complied with the applicable regulations. The planning, administration, and reporting stages are mostly in accordance with the rules, supported by relevant documents and procedures. However, there are still shortcomings at the implementation and accountability stages, such as the absence of several official documents like the 2024 DPA and the unavailability of a complete SK for task assignments to village officials. Additionally, public involvement and transparency in delivering information still need improvement. These findings suggest the importance of strengthening documentation management and increasing the capacity of village officials through training and technical assistance.